2018
DOI: 10.1007/s40204-018-0105-2
|View full text |Cite
|
Sign up to set email alerts
|

Study of physico-chemical properties and in vitro antimicrobial activity of hydroxyapatites obtained from bone calcination

Abstract: Hydroxyapatite was obtained by bone calcinations. To study the calcination process, bovine and porcine bones were first autoclaved to remove fat and other non-bone tissues. They were then heated in an alumina pan in an oxidizing atmosphere of air, where simultaneous thermal analysis curves were recorded. To prepare the hydroxyapatites, bone samples were calcined at 850 °C and 1000 °C using a muffle furnace for 1 h. The obtained materials were powdered using mortar and pestle, and sifted in a sieve (60 mesh) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…The maximum content of the mineral composition of natural bone is comprised of hydroxyapatite [Ca 10 (PO 4 ) 6 (OH) 2 ] nanocrystal structure (Dorozhkin 2016 ). Several studies have reported that calcium phosphates and their complexes such as hydroxyapatite can present a desired environment for bone tissue regeneration due to their likeness to the chemical composition of natural bone, tooth, and enamel (Manafi and Joughehdoust 2009 ; Stabile 2016 ; Chen 2017 ; Khoshakhlagh 2017 ; Resmim et al 2018 ). It was found that the addition of fluoride ions into hydroxyapatite structure increases its resistance to biodegradability significantly (Joughehdoust et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum content of the mineral composition of natural bone is comprised of hydroxyapatite [Ca 10 (PO 4 ) 6 (OH) 2 ] nanocrystal structure (Dorozhkin 2016 ). Several studies have reported that calcium phosphates and their complexes such as hydroxyapatite can present a desired environment for bone tissue regeneration due to their likeness to the chemical composition of natural bone, tooth, and enamel (Manafi and Joughehdoust 2009 ; Stabile 2016 ; Chen 2017 ; Khoshakhlagh 2017 ; Resmim et al 2018 ). It was found that the addition of fluoride ions into hydroxyapatite structure increases its resistance to biodegradability significantly (Joughehdoust et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because the intensity of the scattered x-rays is measured at higher angles, the collimation and flight path requirements are more compact for a dedicated WAXS instrument relative to instruments optimized for Briefly, in the direct contact method a bacterial suspension is transferred to a vial containing the material and then the mixture is spread onto agar plates and incubated for several hours. After this period, the number of bacterial colonies on each plate is counted and compared against growth-positive control in absence of materials [Resmin et al, 2019]. The disc diffusion test is performed on an agar plate containing sterilized filter paper discs, which have been previously treated and soaked with Hap nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
“…A similar result was reported by Balu et al, 6 the susceptibility to E. coli and S. aureus was studied and ZOI was found to be 13 and 14.5 mm, respectively, at 50 mg/mL of nano-HAp synthesized from cuttlefish bone. Resmim et al 35 showed a growth inhibitory effect of S. aureus up to 81% and 56% by using nano-HAp from the bovine and porcine bone obtained by calcination at 1273 K, respectively.…”
Section: Antimicrobial Properties Of Nano-hapmentioning
confidence: 99%
“…Although various properties of HAp including antibacterial properties depend on the size, surface area, morphology, porosity, crystallinity, stoichiometry, and types and concentration of ions present in it 6,10,35 , many of the researches reported that the antibacterial activity of nano-HAp is enhanced by doping with other elements like Zn, Cu, Ag, Co, Ce, Se, etc. 10,30,40,60 Hence different ions and its concentration present in the nano-HAp may play a crucial role in inhibiting the bacterial growth 32,33 along with other properties such as morphology, size, etc.…”
Section: Antimicrobial Properties Of Nano-hapmentioning
confidence: 99%